Impaired chronotropic response to physical activities in heart failure patients. Issue 1 (December 2017) - Shen, Hong; Zhao, Jianrong; Zhou, Xiaohong; Li, Jingbo; Wan, Qing; Huang, Jing; Li, Hui; Wu, Liqun; Yang, Shungang; Wang, Ping
Abstract Background While exercise-based cardiac rehabilitation has a beneficial effect on heart failure hospitalization and mortality, it is limited by the presence of chronotropic incompetence (CI) in some patients. This study explored the feasibility of using wearable devices to assess impaired chronotropic response in heart failure patients. Methods Forty patients with heart failure (left ventricular ejection fraction, LVEF: 44.6 ± 5.8; age: 54.4 ± 11.7) received ECG Holter and accelerometer to monitor heart rate (HR) and physical activities during symptom-limited treadmill exercise testing, 6-min hall walk (6MHW), and 24-h daily living. CI was defined as maximal HR during peak exercise testing failing to reach 70% of age-predicted maximal HR (APMHR, 220 – age). The correlation between HR and physical activities in Holter-accelerometer recording was analyzed. Results Of 40 enrolled patients, 26 were able to perform treadmill exercise testing. Based on exercise test reports, 13 (50%) of 26 patients did not achieve at least 70% of APMHR (CI patients). CI patients achieved a lower % APMHR (62.0 ± 6.3%) than non-CI patients who achieved 72.0 ± 1.2% of APMHR (P < 0.0001). When Holter-accelerometer recording was used to assess chronotropic response, the percent APMHR achieved during 6MHW and physical activities was significantly lower in CI patients than in non-CI patients. CI patients had a significantly shorter 6MHW distance and less physical activity intensity than non-CI patients. Conclusion The study found impaired chronotropic response in 50% of heart failure patients who took treadmill exercise testing. The wearable Holter-accelerometer recording could help to identify impaired chronotropic response to physical activities in heart failure patients. Trial registration ClinicalTrials.gov IDNCT02358603 . Registered 16 May 2014.